2017
DOI: 10.4067/s0718-95162017000300017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rainfall intensity and rock fragment cover on soil hydrological responses in Central Chile

Abstract: In Chile, 60% of the usable land is affected by erosion and the effects of rock fragment cover, however protecting the soil against these degradation processes have been sparsely studied. Understanding the effects of rainfall intensity and rock fragment cover on soil hydrological processes is a major challenge for the formulation and implementation of proper soil conservation plans. The effects of rock fragment cover on soil erosion rate, surface runoff, sediment concentration and infiltration rate were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Climate change and human activities in the basin can alter the source, formation, quantity, and transport of river runoff and sediment (X. C. Ye et al, 2020). Increasing temperatures accelerate the hydrological cycle, alter precipitation and evapotranspiration patterns, and increase the frequency of extreme weather conditions (Jiao et al, 2022), Heavy precipitation deepens soil erosion and runoff production and confluence effects in the basin, increasing the amount of sediment in the river (Azari et al, 2016; von Bennewitz & Aladro, 2017). With global industrialization, the scope of human transformation of nature is expanding, and its impact is becoming more far‐reaching.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change and human activities in the basin can alter the source, formation, quantity, and transport of river runoff and sediment (X. C. Ye et al, 2020). Increasing temperatures accelerate the hydrological cycle, alter precipitation and evapotranspiration patterns, and increase the frequency of extreme weather conditions (Jiao et al, 2022), Heavy precipitation deepens soil erosion and runoff production and confluence effects in the basin, increasing the amount of sediment in the river (Azari et al, 2016; von Bennewitz & Aladro, 2017). With global industrialization, the scope of human transformation of nature is expanding, and its impact is becoming more far‐reaching.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have presented the development, calibration, and use of RSs for a wide range of purposes, such as agricultural research [17][18][19][20][21][22]; biomass studies [23,24]; infil-Sustainability 2021, 13, 3060. https://doi.org/10.3390/su13063060 https://www.mdpi.com/journal/sustainability Sustainability 2021, 13, 3060 2 of 22 tration analysis [14,15,25,26]; urban hydrology simulation, including permeable pavement performance [27], evaluation of processes of accumulation and transport of pollutants on pavements and roof surfaces [28][29][30][31][32]; and rainwater quality research. RSs are frequently used in geotechnical evaluations of soil loss and erosion [1,16,22,[33][34][35][36][37][38], slope stability [13,39,40] and infiltration, and percolation in unsaturated soils [12,14,15,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the soil nutrient content and composition are impacted by erosion transport, which further affects the global biogenic factor cycle 68 . Thus, soil erosion is among the major ecological and environmental problems worldwide 9,10 . Soil erosion is affected by various factors, including the rainfall intensity, topography, soil properties, land cover and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Von-Bennewitz et al . 9 indicated that gravel cover contributed to delaying the start time of surface runoff, and showed that the amount of surface runoff was directly proportional to the rainfall intensity and inversely proportional to the gravel coverage degree. However, the results may differ with a high gravel coverage degree.…”
Section: Introductionmentioning
confidence: 99%